2009
DOI: 10.1093/cercor/bhp215
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of the Spatial and Expectancy Components of Endogenous and Stimulus-Driven Orienting of Attention in the Posner Task

Abstract: Voluntary orienting of visual attention is conventionally measured in tasks with predictive central cues followed by frequent valid targets at the cued location and by infrequent invalid targets at the uncued location. This implies that invalid targets entail both spatial reorienting of attention and breaching of the expected spatial congruency between cues and targets. Here, we used event-related functional magnetic resonance imaging (fMRI) to separate the neural correlates of the spatial and expectancy compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
173
5
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(203 citation statements)
references
References 35 publications
19
173
5
6
Order By: Relevance
“…These clusters were found in parietal and frontal cortex, overlapping with the typical core nodes of the dorsal and ventral attention network. Matching the characteristics of the behavioral paradigm, dorsal attention network nodes in the posterior parietal cortex and the precentral sulcus (presumably the frontal eye field) were activated, most likely reflecting the orientation of attention toward the location of the upcoming target stimulus, which was shown in many previous neuroimaging studies using traditional spatial orienting paradigms (Doricchi, Macci, Silvetti, & Macaluso, 2010; Hopfinger, Buonocore, & Mangun, 2000; Kincade, Abrams, Astafiev, Shulman, & Corbetta, 2005). Similarly, ventral attention network nodes in inferior parietal and frontal cortex were activated, in particular, during anti‐cue trials, most likely reflecting the control over “distracting” anti‐cues and the reorientation toward the target stimulus.…”
Section: Discussionsupporting
confidence: 54%
“…These clusters were found in parietal and frontal cortex, overlapping with the typical core nodes of the dorsal and ventral attention network. Matching the characteristics of the behavioral paradigm, dorsal attention network nodes in the posterior parietal cortex and the precentral sulcus (presumably the frontal eye field) were activated, most likely reflecting the orientation of attention toward the location of the upcoming target stimulus, which was shown in many previous neuroimaging studies using traditional spatial orienting paradigms (Doricchi, Macci, Silvetti, & Macaluso, 2010; Hopfinger, Buonocore, & Mangun, 2000; Kincade, Abrams, Astafiev, Shulman, & Corbetta, 2005). Similarly, ventral attention network nodes in inferior parietal and frontal cortex were activated, in particular, during anti‐cue trials, most likely reflecting the control over “distracting” anti‐cues and the reorientation toward the target stimulus.…”
Section: Discussionsupporting
confidence: 54%
“…It has been suggested that the preferential activation of the right hemisphere leads to leftward attentional bias, but the functional lateralization is by no means universal and does not apply to the entire frontoparietal attentional networks (Doricchi et al, 2010;Shulman et al, 2010). Interestingly, functional neuroimaging studies not only point to hemispheric asymmetries in the representation of visual space in VSTM and spatial attention, especially within the posterior parietal cortex, but also indicate task-dependent and topographic region-dependent properties of these asymmetries.…”
Section: Lateralization Of Frontoparietal Networkmentioning
confidence: 99%
“…Existing studies that have examined the brain networks underlying detection of behaviorally relevant stimuli have generally defined "relevance" by target features, for example, targets in unexpected locations (Arrington et al, 2000;Kincade et al, 2005;Vossel et al, 2006;Indovina and Macaluso 2007;Doricchi et al, 2010), target-colored distracters (Serences et al, 2005;Hu et al, 2009), or target-relevant cues (Shulman et al, 2009;Geng and Mangun, 2011). These studies have identified a right-lateralized ventral frontoparietal network, including the temporoparietal junction (TPJ) and inferior frontal gyrus (IFG) (Corbetta and Shulman, 2002;Fox et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to frequent (but less emphasized) coactivation with right TPJ, left TPJ has been hypothesized to orient attention toward stimuli that match a target "template" (Doricchi et al, 2010), relative target saliency , or episodic memories (particularly verbal ones) (Cabeza et al, 2008;Ciaramelli et al, 2008;Hutchinson et al, 2009;Ravizza et al, 2011). These hypothesized roles for left TPJ share the theme of encoding non-visuospatial, task-relevant features.…”
Section: Introductionmentioning
confidence: 99%